ChemInform Abstract: Catalyst‐Free Intramolecular Formal Carbon Insertion into σ‐C—C Bonds: A New Approach Toward Phenanthrols and Naphthols. Issue 29 (1st July 2013) - Xia, Ying; Qu, Peiyuan; Liu, Zhenxing; Ge, Rui; Xiao, Qing; Zhang, Yan; Wang, Jianbo
Abstract: The novel methodology allows the conversion of biphenyl carbaldehydes and related heterocyclic compounds into hydroxy‐substituted polycyclic aromatic products.